MAKNA UPACARA NYELAMAK DILAOK SEBAGAI ASET BUDAYA (STUDI FENOMENOLOGI) - Lestari, Intan Dwi (RISTANSI: Riset Akuntansi, 2024)
This study aims to understand the meaning of assets in the Nyelamak Dilaok Ceremony from an accounting perspective using a qualitative approach with phenomenological methodology. This approach enables an in-depth exploration of experiences and cultural meanings associated with the ceremony. Data were collected through in-depth interviews, participant observation, and field notes, and analyzed using phenomenological methods to identify patterns in participants' perceptions of the ceremony. The findings reveal that the Nyelamak Dilaok Ceremony is a cultural asset with value in cultural, spiritual, and community sustainability contexts. These insights provide a deeper understanding of the significance of the ceremony as part of cultural heritage and its relevance to accounting. The study highlights the role of culture in community life and the importance of appreciating the cultural values of traditional practices. The findings are expected to serve as a foundation for managing and preserving significant cultural heritage for the communities involved.